Sign Order in Slovenian Sign Language Transitive and Ditransitive Sentences - Pavlič, Matic (Studies in Polish linguistics, 2020)
Podstawowy szyk zdania w słoweńskim języku migowym (SZJ) to szyk podmiot-orzeczenie-dopełnienie (SVO). Wskazuje na to analiza zdań bez topikalizacji czy fokalizacji, zawierających czasowniki przechodnie i dwuprzechodnie, wyprodukowanych w trakcie zadania polegającego na opisie obrazów (Picture Description Task) przez informatorów, których pierwszym językiem jest SZJ. Dane pokazują również, że modalność wizualno-gestowa, z której korzysta SZJ, ma wpływ na linearyzację, ponieważ predykaty klasyfikujące oparte na modalności wizualnej wymagają użycia nacechowanego w tym języku szyku SOV.ABSTRACT The basic sign order in Slovenian Sign Language (SZJ) is Subject-Verb-Object (SVO). This is shown by analysing non-topicalised or focalised transitive and ditransitive sentences that were elicited from first language SZJ informants using Picture Description Task. The data further reveal that the visual-gestural modality, through which SZJ is transmitted, plays a role in linearization since visually influenced classifier predicates trigger the non-basic SOV sign order in this language.